Elementary excitations in solid oxygen (Review Article): - Freiman, Yu. A.; Jodl, H. J. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2002)
Theoretical results on lattice excitations in solid oxygen at equilibrium vapor pressure are reviewed with the emphasis on the behavior of phonons, librons and magnons in the orientationally and magnetically ordered a-phase. Results on magnetooptics of solid oxygen and their impact on advance of magnetic studies of solid oxygen are briefly reviewed. Some results under discussion are new: among these are theoretical results on the magnon heat capacity, the analysis of the behavior of librons at the a-b transition, anisotropy of the spectrum of magnons.